2015
DOI: 10.1371/journal.pntd.0003529
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology and Molecular Characterization of Cryptosporidium spp. in Humans, Wild Primates, and Domesticated Animals in the Greater Gombe Ecosystem, Tanzania

Abstract: Cryptosporidium is an important zoonotic parasite globally. Few studies have examined the ecology and epidemiology of this pathogen in rural tropical systems characterized by high rates of overlap among humans, domesticated animals, and wildlife. We investigated risk factors for Cryptosporidium infection and assessed cross-species transmission potential among people, non-human primates, and domestic animals in the Gombe Ecosystem, Kigoma District, Tanzania. A cross-sectional survey was designed to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
5
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 51 publications
10
95
5
4
Order By: Relevance
“…Previous studies also found that raising cattle, especially calve, was a risk factor for human Cryptosporidium infection. 3,31 In this area, cattle usually graze on the nearby hills away from human settlements, thus human-cattle contacting is less frequent. Horses, cats, and dogs are primarily infected with host-specific Cryptosporidium species or genotypes, and therefore, the actual risk of zoonotic transmission of these animals may be low.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also found that raising cattle, especially calve, was a risk factor for human Cryptosporidium infection. 3,31 In this area, cattle usually graze on the nearby hills away from human settlements, thus human-cattle contacting is less frequent. Horses, cats, and dogs are primarily infected with host-specific Cryptosporidium species or genotypes, and therefore, the actual risk of zoonotic transmission of these animals may be low.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the total of 31 analyzed stool samples, 18 (58.06%) were positive, results much higher than those found by other authors in different parts of the world, ranging from 0.5 to 27% (SAK et al, 2013;. SALYER et al, 2012;PARSONS et al, 2015;EKANAYAKE et al, 2006). These authors claim that environmental changes caused by man and the use of these means by humans and animals provide a transmission of parasitic infection between wild and domestic animals and man.…”
Section: Resultsmentioning
confidence: 65%
“…Both zoonotic transmission of pathogens and composition of parasite communities in mammals have been linked to human disturbances, as previously outlined [Patz et al, 2000;Chapman et al, 2005;Puttker et al, 2008;Zommers et al, 2013;Helenbrook, 2014;Parsons et al, 2015; reviewed by Han et al, 2016]. In particular, parasite species richness and prevalence of several intestinal parasites have been reported to be higher in selectively logged and forest fragments compared to primary habitat Salzer et al, 2007;Trejo-Macías et al, 2007;Schwitzer et al, 2010]; however, there are several cases where no effect was found -particularly as it relates to primates [Kowalewski and Gillespie, 2009;Young et al, 2013].…”
Section: Introductionmentioning
confidence: 94%